Epistemologi Pendidikan Agama Islam: Perbandingan Pola Pendidikan Sahabat Rasulullah Shallallahu ‘Alaihi Wasallam Dengan Paradigma Pendidikan Modern - Makrom, Choirul; Ainirrohmah, Nurul; Arridho, Afrikhun Rizki; Shafiyyah; Khoiriyah (Educational Research Center, 2026)
The development of contemporary Islamic education faces significant challenges arising from modernity, the Industrial Revolution 4.0, Society 5.0, and Artificial Intelligence (AI), which generate epistemological issues concerning the relationship between knowledge, values, and technology. This article aims to analyze and compare the epistemological structure of education during the era of the Prophet Muhammad and his Companions with the modern educational paradigm, and to formulate an integrative epistemological synthesis for Islamic Religious Education (IRE). This study employs a qualitative library research approach with comparative analysis of classical and contemporary Islamic education literature. The findings indicate that the educational model of the Companions reflects a normative-practical epistemological structure grounded in tawhid as its ontological foundation, the Qur’an as the primary source of knowledge, and moral character (akhlaq) and adab as its axiological orientation. Exemplary conduct (uswah), spiritual purification (tazkiyat al-nafs), and ethical teacher–student relationships function as central mechanisms for internalizing values. In contrast, the modern educational paradigm is characterized by systemic modernization, technological integration, interdisciplinary approaches, and positivistic methodological tendencies that risk leading to the desacralization of knowledge and value fragmentation if detached from a tawhidic framework. The comparison reveals that the fundamental difference lies in epistemological orientation and criteria of educational success. Therefore, an integrative epistemology of Islamic Religious Education is required—one that combines curricular and technological innovation with the normative foundations of Islam through the integration of faith and knowledge, reinforcement of adab, and digital ethical literacy. Such synthesis enables Islamic education to remain adaptive to modernity while consistently fostering the cognitive, ethical, and spiritual wholeness of learners.